2019
DOI: 10.1016/j.ypmed.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging technology to address the problem of cigarette smoking among women of reproductive age

Abstract: Women of reproductive age and particularly pregnant women underutilize evidence-based smoking cessation services such as counseling and quit lines. Mobile health (mHealth) may constitute an unexplored and innovative avenue for providing smoking cessation support to a population that is otherwise difficult to reach with evidence-based interventions. Female respondents aged 18–44 years (N = 10 023) were drawn from the first wave of the Population Assessment of Tobacco and Health (PATH) study (2013–2014). We exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…As with many other fields of study, mHealth approaches to promoting behavior change continue to grow in the tobacco field. Although much of this work focuses on reducing tobacco use among the general population, one recent report found that a U.S. national sample of both nonpregnant women of childbearing age and pregnant women who smoked used various digital forms (e.g., social media, text messaging, smartphone apps) at similar rates as both their nonsmoking counterparts and the general U.S. population (Kurti, Bunn, Nighbor, et al, 2019). These findings provide support for the potential utility of leveraging technology to deploy tobacco prevention, education, and treatment efforts to reduce tobacco use among reproductive-aged women.…”
Section: Tobacco Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…As with many other fields of study, mHealth approaches to promoting behavior change continue to grow in the tobacco field. Although much of this work focuses on reducing tobacco use among the general population, one recent report found that a U.S. national sample of both nonpregnant women of childbearing age and pregnant women who smoked used various digital forms (e.g., social media, text messaging, smartphone apps) at similar rates as both their nonsmoking counterparts and the general U.S. population (Kurti, Bunn, Nighbor, et al, 2019). These findings provide support for the potential utility of leveraging technology to deploy tobacco prevention, education, and treatment efforts to reduce tobacco use among reproductive-aged women.…”
Section: Tobacco Controlmentioning
confidence: 99%
“…In addition to providing women with co-occurring vulnerabilities with access to intensive, evidence-based tobacco cessation treatment, efforts must also be made to address competing needs in the lives of these women so that they can fully engage in the treatments that are made available to them (Levinson et al, 2015). Although mHealth interventions may help surmount geographical barriers to accessing tobacco cessation treatment, it is worth noting that socioeconomic barriers in access to varying digital forms (e.g., smartphone ownership) are still present, with nonpregnant and pregnant smokers both endorsing less access relative to their nonsmoking counterparts, although digital form utilization among these women was still quite high (Kurti, Bunn, Nighbor, et al, 2019). Nonetheless, it will be important for those developing technology-based smoking cessation services to devise explicit plans for engaging smokers who remain in the minority without access to various digital platforms (e.g., directing them to locations in their community that offer free computer and Internet access (McInnes, Li, & Hogan, 2013), or programs that distribute free mobile phones to low-income persons; Komando, 2012).…”
Section: Related Research and Challenges In A Changing Tobacco Landscapementioning
confidence: 99%
“…Smoking in women carries the risk of diseases such as cervical cancer, osteoporosis, cardiovascular disease, atherosclerosis, and type 2 diabetes, lung cancer, premature menopause, premature birth, abnormal fetal growth, low birth weight, miscarriage, and increases fetal death [ 3 , 4 ]. Women who smoke before and during pregnancy increase the risk of preterm birth, abnormal fetal growth, low birth weight, miscarriage, and fetal death [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with existing research, both US and UK women were regular and skilled users of technology, using apps to track fitness (steps), accessing information on breastfeeding via websites and apps, and using electronic means of forming and maintaining social networks, and linking online to "real world" social groups (Johnson, 2015;Kurti et al, 2019). In general, the qualitative data revealed that technology was a facilitator-a means to promote positive health behaviours and to provide support for women adapting to a postpartum identity.…”
Section: Discussionmentioning
confidence: 67%